STUDI DISTRIBUSI UDARA PENDINGIN REEFER CONTAINER IKAN PADA KERETA API MENGGUNAKAN CFD - Cynthia Cahya Aditama; Alfi Tranggono Agus Salim; Rahayu Mekar Bisono; Luthfi Hakim; Sabdono Abdi Sucipto; Firdausa Retnaning Restu (P3M Politeknik Negeri Indramayu, 2023)
Fresh fish is sensitive to storage temperature. Temperatures above 2 °C accelerate the growth of bacteria and cause spoilage. The optimal storage temperature for frozen fish is -20 °C. Reefer container with a closed cooling system serves to preserve by maintaining the temperature of frozen fish. The problem of this research is the uneven distribution of cold air in the reefer containers of the train, thereby reducing the quality of frozen fish. The purpose of this research is to increase the even distribution of air, velocity, and pressure in the reefer container of the train. The solution to the problem is simulation and analysis of the condition of the reefer container train using Computational Fluid Dynamics (CFD). Reefer containers without guide plates are simulated to find out the area of the train reefer containers that are not evenly distributed. The distribution of air in the reefer container of the train is improved even by the addition of guide plates with variations in angles of 40°, 50°, and 60°. This research produces qualitative data (velocity contour and pressure contour reefer container) and quantitative (average velocity and pressure). The results of this study are CFD simulation data of uniform distribution of air, speed, and pressure on the reefer container train with a 40⁰ guide plate.